Main concepts of sustainable development and mountainous regions (on the example of the Caucasus) - Nodar Elizbarashvili; Nino Sulkhanishvili; Rusudan Elizbarashvili (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
Main concepts of sustainable development are focused on: The economic problems (sustainable development relies on and considers the rational use of exhaustible natural resources, development of resource-saving technologies, focus on inexhaustible and restorable resources, ecological production, minimization and reuse of waste); The social problems (sustainable development relies on and considers the stability of social and cultural systems, environmentally friendly and legally justified use of the national wealth, protection of cultural and historical values, publicity of decisions and maximum engagement of the society in the planning and man-agement process); The ecological problems (sustainable development relies on and considers the integrity of ecological (biological, landscape) environment, maintenance of the viability and functioning mechanisms of ecosystems, improvement of stability and self-restoration mechanisms of the natural environment, due determination of the social-economic functions of the natural landscapes, ecology-oriented territorial (landscape) planning, landscape service and management, creation of the esthetic environment). All three concepts of sustainable development, despite the diversity of the considered issues, can be considered as components of a single sys-tem. They are interconnected and mutually determinative, and consequently, sustainable development, as a problem, is quite difficult to solve and is a long civic and scientific process, with more than one scientific branch related to it considering the objectives and opportunities of sustainable development at either branch, or component level. Caucasia is one of the most important natural, ecological, geopolitical, religious, ethnic, transport, etc. crossroads of the world. The Caucasia plays one of the most important geopolitical roles in the modern world, particularly in the Near East and West-ern Asia. Its role is also essential in the economic relations; however, this role is diminished by the different developmental trends of the countries of the region. The problems of the sustainable development of the Caucasia can be solved only at the expense of the cooperation between the countries of the region.